Human UDP‐Glucuronosyltransferases 1A1, 1A3, 1A9, 2B4 and 2B7 are Inhibited by Diethylstilbestrol. Issue 5 (8th June 2016) - Zhu, Liangliang; Xiao, Ling; Li, Wenjuan; Zhang, Yuan; Han, Wenwen; Zhu, Yu; Ge, Guangbo; Yang, Ling
Abstract: Inhibition of UDP‐glucuronosyltransferases (UGTs) can result in many undesired side effects. Diethylstilbestrol (DES), a synthetic oestrogen famous for its multiple toxicities, was once widely administered to women in high dosages and now still gains application in clinics. This study investigated in vitro inhibitory effects of DES on catalytic activities of human UGTs, aiming at disclosing new potential toxic mechanisms on the basis of interactions between DES and metabolizing enzymes. DES (10 μM) could decrease activities of UGT1A1, 1A3, 1A9, 2B4 and 2B7 in catalysing 4‐methylumbelliferone (4‐Mu) glucuronidation. Further kinetic analyses showed that inhibition of these UGTs followed competitive (UGT1A1 and 1A9), mixed (UGT1A3 and 2B4) and non‐competitive (UGT2B7) mechanisms, with K i values ranging from 0.91 to 4.1 μM. The inhibition potentials of UGT1A9 and 2B7 in human liver microsomes (HLM) were further tested by employing propofol and zidovudine as probe substrates, respectively. The inhibition of human liver microsomal UGT1A9 followed mixed mechanism, with the K i value of 3.5 μM and α of 4.1. On the other hand, DES displayed non‐competitive inhibition against UGT2B7 in HLM, with the K i value of 9.8 μM. The risks of in vivo inhibition of human UGTs were also predicted by calculation of plasma C/K i values. Results suggest that DES can trigger in vivo inhibition of UGT1A1, 1A3, 1A9, 2B4 and 2B7 after the intravenous administration in high doses.